Wildlife in your backyard- the importance of environmental education in the infant school - Tim Wright (Environmental Association of Southern Africa, 1987)
A number of precepts based on practical experience are suggested for env ironmental education at the pre-school level. The importance of the child's immediate environment is considered and a variety of possible activities are outlined.